Synthesis and Structural Characterization of Biofuel From Cocklebur sp., Using Zinc Oxide Nano-Particle: A Novel Energy Crop for Bioenergy Industry - Ullah, Kifayat; Jan, Hammad Ahmad; Ahmad, Mushtaq; Ullah, Anwar (Frontiers in Bioengineering and Biotechnology, 2020)
This study reports the synthesis and characterization of biofuel from the novel non-edible feedstock cocklebur seeds oil. The Cocklebur crop seeds oil was studied as a potential source for biofuel production based on the chemical, structural and fuel properties analysis. The oil expression and FFAs content in cocklebur crop was reported 37.2% & 0.47 mg KOH/g, using soxhlet apparatus and acid base titration method, respectively. The maximum conversion and yield of the cocklebur crop seeds non-edible oil to biofuel was pursued 93.33%, using transesterification process. The optimum protocol for maximum conversion yield was adjusted: 1:7 oil-methanol molar ratios, ZnO concentration 0.2gm (w/w), reaction temperature 60oC, and reaction time 45 minutes, respectively. Qualitatively, the cocklebur crop synthesized biofuel was quantified and structurally characterized by GC/MS, FT-IR, NMR & AAS spectroscopies. Quantitatively, the fuel properties of cocklebur crop biofuel was analyzed and compared with the international ASTM & EN standards.